PEMBERIAN PROBIOTIK DALAM PAKAN UNTUK BUDIDAYA IKAN LELE - Dyah Hariani; Tarzan Purnomo (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
The purpose of research is produced using probiotic fermented feed that can increase: the growth rate (SGR), and feed efficiency (FCR). The research was conducted in July and November 2016. The research design used is CRD with 4 treatments and 3 replications, consisting of without given a probiotic (0%), probiotics 5%, 10% and 15% of the total feed given, for all waters treatment probiotics added to one liter every single week. Media for microbial growth added "medicinal" (white turmeric, ginger, red ginger) containing bioactive and improve immunity, pineapple source of vitamin C, sugar, bran and molasses energy sources and dairy sources of protein that are suitable for growth and multiply microbes. Parameters: SGR and FCR. Analysis of data using Anova, followed by Duncan test. The results showed probiotics in feed and aquaculture waters have a significant influence on the SGR and FCR (P <0.05). Giving 15% of probiotics produce the best catfish SGR: 3.3867 ± 0, 24440%. Giving 5% probiotics produce the best FCR 1.5733 ± 0.0987. Keywords: Probiotics, SGR, FCR, catfish